Analytical Approaches between New Media and Traditional Media - جاسم مؤيد نصيف (ALBAHITH ALALAMI, 2017)
The research deals with an analytical approach between new media and traditional one in the light of the changes imposed by technology, which has been able to change a number of common concepts in the field of communication and media. The researcher tries to find an analytical explanation of the relationship between technology by being an influential factor in building the information society, which is the basis of new media, and the technical output that influenced the forms of social relations and linguistic construction as a human communication tool. The research deals with an analytical approach between new media and traditional one in the light of the changes imposed by technology, which has been able to change a number of common concepts in the field of communication and media. The researcher tries to find an analytical explanation of the relationship between technology by being an influential factor in building the information society, which is the basis of new media, and the technical output that influenced the forms of social relations and linguistic construction as a human communication tool. The researcher formulated the problem of the research with s set of questions: 1- What is the language of communication in the new media? 2- What is the relationship between new media and the traditional one? The researcher concludes with a number of results. These are as follow: 1- There is a change in the language used in the new media according to the need required by the technical system of social communication2- There is a relationship between the new media and the traditional one based on the mutual need for information and the difference stems from the great ability of the impact of technology in the new media and the continuous adaptation of the elements of the communication process in the new media with technological results3- There is a need to theoretical construction that enables the communication process to progress according to the concept of speed and time as factors in the communication process and a product of the development of technology.